Adaptive dif Modules in Permafrost Strains of Acinetobacter lwoffii and Their Distribution and Abundance Among Present Day Acinetobacter Strains - Sofia Mindlin (Frontiers in Microbiology, 2019)
The dif/Xer system of site-specific recombination allows resolution of chromosomal dimers during bacterial DNA replication. Recently, it was also shown to be involved in horizontal transfer of a few known Xer-dependent mobile elements. Here, we show that plasmids of various Acinetobacter species, including clinically important strains, often contain multiple pdif sites that are mainly located within their accessory regions. Chromosomes of Acinetobacter strains may also contain additional dif sites, and their similarity with plasmid pdif sites is higher than with the main chromosomal site dif1. We further identify putative mobile genetic elements containing pdif sites on both flanks of adaptive genes and analyze their distribution in Acinetobacter species. In total, we describe seven mobile elements containing genes with various adaptive functions from permafrost strains of A. lwoffii group. All of them are also spread in modern plasmids of different Acinetobacter species including A. baumannii. We could not detect pdif sites and corresponding mobile elements in closely related bacterial genera, including Psychrobacter and Moraxella. Thus, the widespread distribution of dif modules is a characteristic feature of Acinetobacter species and may contribute to their high adaptability both in the environment and in the clinic.